Effect of women’s intra-household bargaining power on postnatal and infant healthcare in rural Uganda–Results from a cross sectional survey in Kyenjojo district - Kadengye, Damazo T.; Atahigwa, Catherine; Kampire, Pamela; Mucunguzi, Stephen; Kemigisha, Elizabeth; Nyakato, Viola N.; Kiwuwa-Muyingo, Sylvia (Midwifery, 2020)
Global estimates by the United Nations inter-agency group for child mortality show that as of 2017, under-five mortality rate had decreased by 58%, from an estimated rate of 93 deaths per 10 0 0 live births in 1990 to 39 deaths per 10 0 0 live births. In the same period, Uganda achieved noticeable progress with the risk of a child dying before five years of age decreasing by 71% from 187 to 49 deaths per 10 0 0 live births ( UNICEF Data, 2019 ; You et al., 2015 ), and under five mortality dropped from 177 to 64 per 10 0 0 live births ( Uganda Bureau of Statistics [UBOS] and ICF Interna- tional, 2017 ). Despite significant improvements, utilization of ma- ternal and child healthcare services still remains a major area of concern with substantial disparities amongst women living in de- veloping countries, most especially those in the rural areas with unacceptably low levels of access to services ( Beegle et al., 2001 ; World Health Organisation [WHO], 2016 ). Although utilization of antenatal care services (ANC) is being promoted through interven- tions to enhance attendance and skilled health care at birth, less attention has been given to postnatal care in preventing complica- tions and ensuring better maternal and child health care.
Keywords: healthcare; Kyenjojo district; intra-household